DIGITAL BRAND LOCAL PRODUCT KREESANG 354 THROUGH INSTAGRAM ACCOUNT @KREESANG2WSSAQ354 IN INCREASING BRAND AWARENESS - Besse Mutiara Baso Mattappa; Syamsu Alam; Asmayanti; Agus Syam; Andika Isma (Adiba Aisha Amira, 2025)
This research aims to analyze the use of digital branding strategies on the local product Kreesang 354 through the Instagram account @Kreesang354 in increasing brand awareness. In the current digital era, social media has become an important platform in product marketing, especially for local brands that want to introduce their products to a wider audience. This study examines how Kreesang 354 utilizes Instagram as a tool to build brand image and increase brand awareness among consumers. The method used in this research is a qualitative approach with a case study on the Kreesang 354 Instagram account. Data were obtained through direct observation of the uploaded content, interaction with the audience, as well as analysis of the engagement rate and frequency of interactions occurring on the platform. In addition, interviews with the administrators of the Kreesang 354 Instagram account and several consumers were also conducted to deepen the understanding of the digital branding strategies implemented. The research results show that Kreesang 354 has successfully utilized Instagram as an effective medium to introduce their products by using various features such as feed, stories, and IGTV to create engaging content. Additionally, the use of influencers and collaborations with various parties also contributed to increasing brand interaction and exposure. Thus, this research concludes that Instagram has a significant impact on increasing brand awareness for the local product Kreesang 354.